Morphological, physiological and pathological variations among Sclerotium rolfsii isolates of soybean - S.K. AGNIHOTRI, M.M. ANSARI and (Indian Phytopathology, 2002)
Forty-four isolates of Sclerotium rolfsii [Corticium rolfsii], the causal organism of collar rot of soyabean, obtained from different locations in India were grouped on the basis of morphological characters of the sclerotia and their arrangement onsemi-synthetic medium. On the basis of oxalic acid production in culture filtrates and pathogenicity on different soyabean varieties (cvs. Improved Pellican, Lee, Hardee and Bragg), the isolates were grouped into 12 races. Race I was more dominant than other races and highly virulent to all the varieties. There was a positive correlation between oxalic acid production and the virulence of the isolate.